Singlet fission in tetraaza-TIPS-pentacene oligomers: from fs excitation to μs triplet decay via the biexcitonic state - Alagna, Nicolò; Pérez Lustres, José Luis; Wollscheid, Nikolaus; Luo, Qingqing; Han, Jie; Dreuw, Andreas; Geyer, Florian Ludwig; Brosius, Victor; Bunz, Uwe H. F.; Buckup, Tiago; Motzkus, Marcus (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2019)
Generating two long-living low-energy excitations after absorption of a single high-energy photon has stoked interest in singlet fission (SF) to enhance solar energy conversion in photovoltaics. To this end, survival of the triplet states is critical. This process is investigated in diethynylbenzene-linked tetraaza-triisopropylsilylethynyl-pentacene dimers, for which SF is energetically feasible and facilitated by the close distances between the azapentacenes. The ortho and meta connectivities are explored and compared with the tetraazapentacene molecule and the (1,3,5) trimer. Efficient SF (potential ΦT ≥ 160%) is demonstrated in all oligomers by quantitative kinetic analysis of broadband transient absorption and fluorescence signals. Together with dynamics of the starting singlet, the triplet pair, and the final free triplet state, our results show an intermediate component with spectral properties compatible with a biexcitonic state. Long-living triplets represent only a fraction of the high number of transient triplet pair intermediates, which undergo triplet-triplet annihilation as well as fusion between neighboring pentacenes. Therefore, our work provides new insight into the SF in covalent dimers and paves the way for the application of these materials for carrier multiplication.